902 Too Hot to Handle? Acute Cholecystitis ('Hot Gallbladder') Management and Compliance with NICE Guidelines in A District General Hospital. (4th May 2021) - Karim, S; Tjoakarfa, J; Bondje, S; Jokinen, T; Adegbola, S; Vachlos, G; Tewari, S; Gupta, V
Abstract: Introduction: Current NICE guidelines recommend that patients with acute cholecystitis should be offered laparoscopic cholecystectomy within 1 week of diagnosis. However, the recommendation is often not met within our trust. We aim to investigate our compliance with these guidelines while outlining the complications and cost effects associated with delayed operation. Method: A retrospective study identifying emergency patients presenting with image proven uncomplicated acute cholecystitis was performed. Hospital coding and finance departments were used to obtain this information. Results: 166 patients were identified within a 3-month period. Of which, 85 patients were diagnosed with acute uncomplicated cholecystitis and fulfilled the inclusion criteria. On average, patients waited 108 days for their cholecystectomies (range 14-281). No patients received a cholecystectomy within 1 week of diagnosis. 33 patients re-presented to hospital at least once and the total number of repeated admissions was 51. The average length of stay during readmissions was 6 days (range 1-27). The total cost incurred for those readmissions was £117, 118. Conclusion: : Delayed cholecystectomies for acute cholecystitis increase the likelihood of repeated hospital admissions and place significant strain on resources. Furthermore, it is associated with increased risk of complications. We recommend introducing a weekly 'hot gallbladder list' within our trust dedicated for acute cholecystitis.